The Effect Of Feeding Earthworms With Different Frequencies For Gonadal Maturation Of Beardless Barb (Cyclocheilichthys apogon Val.1842) - Ayu Rayuni Pangaribuan; Nuraini Nuraini; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractThe research was conducted from May to August 2017 at the Fish Hatchery and Breeding Laboratory, Faculty of fisheries and Marine University of Riau Pekanbaru. The purpose of this research was to know the effect of different frequency of earthworm and the best feeding frequency for gonadal maturation of beardless barb (Cyclocheilichthys apogon Val.1842). The research method was experiment method with four treatments and three replications. Control treatment (P0) with 3 times 1 day pellet feeding, treatment 1 (P1) feeding of earthworm 2 times 1 day, treatment 2 (P2) feeding of earthworm 3 times 1 day, treatment 3 (P3) feeding of earthworm 4 times 1 day. The results showed the best treatment was feeding the earthworm of 4 times 1 day frequency. Total fish reached matured stage IV was 10 fish (83.33%), (Gonad Somatic Index 5.61%), Fecundity (8030 eggs) and egg diameter (0.83 mm). The temperature range from 27-310C, pH 5-6, DO 5-7 ppm. Keywords : Beardless Barb (Cyclocheilichthys apogon Val.1842), Earthworms, Gonadal Maturation, Frequency